Pengembangan Produk Dengan Kegiatan Branding Untuk Meningkatkan Pemasaran Pada UMKM Batik Apik Kota Blitar - Jesika Juita Lumban Raja; Sumainah Fauziah (BADAN PENERBIT STIEPARI PRESS, 2023)
The Indonesian nation is known for having abundant natural and cultural resources. Indonesia's rich cultural heritage is a legacy left by the ancestors of the Indonesian nation. Batik is one of the textile products made by the traditional Indonesian people. It can be realized that batik makes a major contribution in creating jobs for Indonesian people. Batik cultural heritage has economic value and can support craftsmen and traders. One of the UMKM datu in Tlumpu Village, namely Batik Apik, has difficulties in product branding and marketing. Therefore, students designed activities and strategies that could help Batik Apik MSMEs in creating digital brands and marketing so that their products would be more widely known. The method used is qualitative with the type of data collection through observation, questionnaires and Focus Group Discussion (FDG). The results of this service activity for Batik Apik SMEs are that SMEs have a brand, namely logos, packaging as well as social media for promotion and marketing such as Facebook, Instagram and websites.